Environmental Role in Shaping Recollection - Bhandari, Krishna Prasad (JODEM: Journal of Language and Literature, 2019)
The core concern of this article is to unravel the underlying mystery of mental activities; it reveals how a writer tends to weave his thoughts and memories. The article aims at dealing with the bases of writer’s reasons and recollections appeared in journal. The analysis as such becomes significant to synchronize, acknowledge and recognize the basic causes behind the seemingly scattered and deviated thoughts but coherently correlated concepts of the writer. In order to achieve such importance and objective of this study, this qualitative research has implemented an outlook the nature / culture ambivalent aspect of the broad perspective, ecocriticism on shaping one’s perception as a tool. And the model text to be analyzed is “Reminiscences of a Journey to Greece” a journal prepared by Govinda Raj Bhattarai. After the investigation into this journal, the exploration elucidates that one’s encounter with the environment becomes the generator and stimulator of mental matters memoirs, concepts, ideas and emotions. Therefore, the key conclusion of this analysis is that one cannot generate ideas in the void or absence of context rather the external world becomes the bedrock to beget inner world the conceptions of the creator in journal.